Endoscopic advanced imaging of the respiratory tract: exploring probe-based confocal laser endomicroscopy in emphysema. Issue 2 (14th April 2017) - Yserbyt, J; Dooms, C; Janssens, W; Verleden, G M
Abstract : Probe-based confocal laser endomicroscopy (pCLE) was performed in 15 patients with emphysema and 15 healthy subjects to visualise small airways in a direct and dynamic way. Morphometry shows that the median cross-sectional area of the alveolar openings at the level of the alveolar ducts is significantly larger in emphysema (7.2×10 4 µm 2 ) as compared with healthy subjects (5.2×10 4 µm 2 ) (p=0.0002). Normalised autofluorescence intensity histograms show a decrease in median autofluorescence intensity (mAFI) in emphysema (p=0.001). mAFI correlates well with Tiffeneau index (r=0.66, p=0.007, 95% CI 0.21 to 0.88). Autofluorescence intensity in emphysema correlates with corresponding data of CT-based quantification. pCLE-based morphometry and autofluorescence intensity analysis in emphysema is able to detect regional changes inside the 'quiet zone'. Trial registration number: Results, NCT01204970 .